Nicotinamide cofactors suppress active-site labeling of aldehyde dehydrogenases - Stiti, N; Chandrasekar, B; Strubl, L; Mohammed, S; Bartels, D; van der Hoorn, R (American Chemical Society, 2016)
Active site labeling by (re)activity-based probes is a powerful chemical proteomic tool to globally map active sites in native proteomes without using substrates. Active site labeling is usually taken as a readout for the active state of the enzyme because labeling reflects the availability and reactivity of active sites, which are hallmarks for enzyme activities. Here, we show that this relationship holds tightly, but we also reveal an important exception to this rule. Labeling of Arabidopsis ALDH3H1 with a chloroacetamide probe occurs at the catalytic Cys, and labeling is suppressed upon nitrosylation and oxidation, and upon treatment with other Cys modifiers. These experiments display a consistent and strong correlation between active site labeling and enzymatic activity. Surprisingly, however, labeling is suppressed by the cofactor NAD(+), and this property is shared with other members of the ALDH superfamily and also detected for unrelated GAPDH enzymes with an unrelated hydantoin-based probe in crude extracts of plant cell cultures. Suppression requires cofactor binding to its binding pocket. Labeling is also suppressed by ALDH modulators that bind at the substrate entrance tunnel, confirming that labeling occurs through the substrate-binding cavity. Our data indicate that cofactor binding adjusts the catalytic Cys into a conformation that reduces the reactivity toward chloroacetamide probes.